Dr. Maria Trapasso — Deep Plane Facelift — Milan - Trapasso, Maria (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Maria Trapasso, practicing in Milan, Italy. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003103; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; italy; milan